The Role of Financial Intermediation in International Trade - Florian Unger (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2016)
This paper highlights that substitution between two types of finance represents an additional channel of adjustment to credit shocks and trade liberalization. Combining firm heterogeneity à la Melitz (2003) with credit frictions based on Holmstrom and Tirole (1997), there is selection of the largest firms into exporting and unmonitored finance, such as public debt or corporate bonds. Smaller producers serve only the domestic market and have to rely on more expensive financial intermediation. The model is consistent with empirical evidence that documents the important role of substitution effects between different sources of external credit. Producers respond to financial shocks by switching the type of finance. These selection effects lead to reallocations of market shares across firms and additional adjustments on the margins of international trade. Furthermore, the model highlights a new source of gains from trade: average productivity increases as falling trade costs allow some exporters to select into cheaper unmonitored finance.
Keywords: F12; G32; L11; 330